Agenda‐setting, policy formulation, and the EU institutional context: The case of the Just Transition Fund. Issue 1 (26th January 2022) - Leppänen, Taru; Liefferink, Duncan
Abstract: Utilizing Kingdon's Multiple Streams Framework (MSF) as a basis, this article aims to further the understanding of the influence institutional factors have on agenda‐setting and policy formulation in the European Union (EU). It does so by analyzing the policy process of the Just Transition Fund (JTF) from agenda‐setting to policy formulation by the Commission. The research finds that policy entrepreneurship is strongly determined by the characteristics and overlap of institutional policy windows. In the JTF case, the institutional context enhanced the influence of policy entrepreneurs within the European Parliament, especially the S&D party, on the combined process of agenda‐setting and policy formulation. Therefore, this paper illustrates that EU MSF scholarship would benefit from taking institutional factors more into account. The conclusions also indicate that supranational institutions can play a larger role in EU climate policy formulation than some of the current research suggests. 摘要: 以金顿的多源流框架（MSF）为基础，本文旨在促进理解制度因素对欧盟议程设置和政策制定的影响。为此，本文分析了从欧盟委员会议程设置到政策制定期间公正转型基金的（JTF）政策过程。研究发现，制度政策之窗的特征及重叠在很大程度上决定了政策企业家的性质（policy entrepreneurship）。在JTF案例中，制度情境提升了欧洲议会中政策企业家（尤其是社会主义者和民主人士进步联盟（S&D party））对议程设置和政策制定这一合并过程的影响力。因此，本文论述认为，欧盟的多源流框架研究将从"对制度因素更多的进行考量"一事中获益。结论还表明，超国家机构能在欧盟气候政策制定一事中发挥更大的作用。 RESUMEN: Utilizando el Marco de Corrientes Múltiples de Kingdon (MSF) como base, este artículo tiene como objetivo promover la comprensión de la influencia que tienen los factores institucionales en el establecimiento de la agenda y la formulación de políticas en la Unión Europea (UE). Lo hace analizando el proceso de políticas del Fondo de Transición Justa (JTF) desde el establecimiento de la agenda hasta la formulación de políticas por parte de la Comisión. La investigación encuentra que el emprendimiento de políticas está fuertemente determinado por las características y la superposición de las ventanas de políticas institucionales. En el caso del JTF, el contexto institucional mejoró la influencia de los empresarios políticos dentro del Parlamento Europeo, especialmente el partido S&D, en el proceso combinado de establecimiento de agenda y formulación de políticas. Por lo tanto, este documento ilustra que la beca MSF de la UE se beneficiaría si se tuvieran más en cuenta los factores institucionales. Las conclusiones también indican que las instituciones supranacionales pueden desempeñar un papel más importante en la formulación de políticas climáticas de la UE de lo que sugieren algunas de las investigaciones actuales.